NETWORKS OF SOCIOLINGUISTICS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
Before looking at the importance of sociolinguistics, we should pay attention to the terms "internal" and "external" in sociolinguistics. If a society uses its own language of the nation and the state, it is an internal language, and if a society uses second and third languages besides its mother tongue, it is a foreign language.